Evolution of phase assemblage of blended magnesium potassium phosphate cement binders at 200° and 1000°C. (October 2015) - Gardner, L. J.; Lejeune, V.; Corkhill, C. L.; Bernal, S. A.; Provis, J. L.; Stennett, M. C.; Hyatt, N. C.
Abstract : The fire performance of magnesium potassium phosphate cement (MKPC) binders blended with fly ash (FA) and ground granulated blast furnace slag (GBFS) was investigated up to 1000°C using X-ray diffraction, thermogravimetric analysis and SEM techniques. The FA/MKPC and GBFS/MKPC binders dehydrate above 200°C to form amorphous KMgPO4, concurrent with volumetric and mass changes. Above 1000°C, additional crystalline phases were formed and microstructural changes occurred, although no cracking or spalling of the samples was observed. These results indicate that FA/MKPC and GBFS/MKPC binders are expected to have satisfactory fire performance under the fire scenario conditions relevant to the operation of a UK or other geological disposal facility